Translation for tourism : language perspectives and translation approach (CV. Zahir Publishing, 2019)
Translatin in the tourism industry has been discussed by translation scholars from number of aspects including the tourism discourse and hoe should be consdidered for translation. This book organized by 5 five chapters, fist chapter describes on the definition of translation. second chapter, explaines the language of tourism, thid chapter, provides analysis the choice intourism text. fourt, discusses translation in tourism, and fifth, conclutions about this topic.